Remembering the Reformation / an inquiry into the meanings of protestantism - Howard, Thomas Albert; Cummings, Brian; Law, Ceri; Riley, Karis; Walsham, Alexandra, 1966- (Oxford Oxford university press, 2016)
"This stimulating volume explores how the memory of the Reformation has been remembered, forgotten, contested, and reinvented between the sixteenth and twenty-first centuries. Remembering the Reformation traces how a complex, protracted and unpredictable process came to be perceived, recorded, and commemorated as a transformative event. From local to global patterns of memory, the contributors examine the ways in which the Reformation embedded itself in the historical imagination and analyse the enduring, unstable and divided legacies that it engendered. The book also underlines how modern scholarship is indebted to processes of memory-making initiated in the early modern period and challenges the conventional models of periodization that the Reformation itself helped to create. This collection of essays offers an expansive examination and theoretically engaged discussion of concepts and practices of memory and Reformation. This volume is ideal for upper level undergraduates and postgraduates studying the Reformation, Early Modern Religious History, Early Modern European History, and Early Modern Literature"--
Includes bibliographical references and index.
Keywords: Reformation -- Anniversaries, etc; Protestantism